The Influence of Transformational Leadership, Work Discipline, and Work Conflict on Police Organizational Performance: Evidence from Subbagpamkol Yanma Polri - Wayan Nuanda (Priviet Social Sciences Journal, 2025)
This study examines the influence of transformational leadership, work discipline, and work conflict on organizational performance at Subbagpamkol Yanma Polri. Improving performance in public sector institutions requires effective leadership, consistent discipline, and proper conflict management. This research adopts a quantitative approach using survey data collected from 108 police personnel through probability sampling. Data were analyzed using multiple linear regression to test both partial and simultaneous effects of the independent variables. Classical assumption tests were conducted to ensure model validity. The results show that transformational leadership and work discipline have a positive and significant effect on organizational performance, indicating that leadership quality and employee discipline are key drivers of performance improvement. In contrast, work conflict has a positive but not significant effect, suggesting that conflict does not strongly influence performance in this context. Simultaneously, all independent variables significantly affect organizational performance. These findings highlight the importance of strengthening leadership practices and maintaining discipline while managing conflict effectively. This study contributes to public sector management literature and provides practical insights for improving organizational performance in law enforcement institutions.